2022
DOI: 10.1155/2022/4930355
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Associations of Metabolic Score for Insulin Resistance Index with Nonalcoholic Fatty Liver Disease among a Nonobese Chinese Population: Retrospective Evidence from a Population-Based Cohort Study

Abstract: Purpose. This study is aimed at investigating the association between the metabolic score for insulin resistance (METS-IR) index and nonalcoholic fatty liver disease (NAFLD) in the nonobese population and its predictive value. Methods. 10730 nonobese subjects were selected from longitudinal cohort research conducted from January 2010 to December 2014. Cox proportional hazards models were employed to assess the relationship between METS-IR and new-onset NAFLD. Generalized additive models were used to identify n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 54 publications
2
22
1
Order By: Relevance
“…Variables with VIF > 5 were considered inappropriate for inclusion in the Cox regression model. 43 , 44 We eliminated two variables with multicollinearity (AHI, and Cr). Three multivariate Cox proportional hazard regressions were established to estimate the independent association between baseline the TyG-WC and the risk of first MI, and hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Variables with VIF > 5 were considered inappropriate for inclusion in the Cox regression model. 43 , 44 We eliminated two variables with multicollinearity (AHI, and Cr). Three multivariate Cox proportional hazard regressions were established to estimate the independent association between baseline the TyG-WC and the risk of first MI, and hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, homeostatic model assessment for IR (HOMA-IR) and other non-insulin-based indices for assessing IR, such as the triglyceride-glucose (TyG) index and metabolic score for IR (METS-IR), were developed for use instead of the hyperinsulinemic–euglycemic clamp technique. Several studies have reported the usefulness of three indicators separately as surrogates for NAFLD [ 9 , 10 , 11 ]. However, the relationship between markers related to IR and liver fibrosis is more complex.…”
Section: Introductionmentioning
confidence: 99%
“…METS-IR was first mentioned in 2018 and is considered to be a reliable and intuitive predictor of IR ( 14 , 15 , 31 ). In recent years, multiple studies have indicated that insulin resistance can cause asthma onset or exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding is limited by the small sample size and requires further confirmation by a multicenter prospective study of a large sample. METS-IR was first mentioned in 2018 and is considered to be a reliable and intuitive predictor of IR (14,15,31). In recent years, multiple studies have indicated that insulin resistance can cause asthma onset or exacerbation.…”
Section: Discussionmentioning
confidence: 99%